Nutritional Management of Milk Fever in Dairy Animals - Das, Lalatendu Keshary; Mohapatra, Narayan (Indian Farming, 2015)
The best three methods that can be implemented for milk fever prevention programme are oral calcium drenching around calving, use of anionic salts (acidifying rations) during close-up dry period and feeding low calcium diet during dry period. Unfortunately, in our country, these methods are rarely put into practice, resulting in low efficacy measures. Apart from problems like low palatability and difficulty in formulating low calcium diets, economic conditions and time consuming processes are the major constrains in this aspect. Lack of organized dairy farms is also a reason for not implementing milk fever control procedures in India. These issues should be thoroughly considered before selecting the method for milk fever prevention in a farm.